2005
DOI: 10.1007/s10733-005-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Focused electron beam-induced deposition of iron- and carbon-containing nanostructures from triiron dodecacarbonyl vapor

Abstract: 93-96. Original Russian Text Copyright © 2005 by Bruk, Zhikharev, Grigor'ev, Spirin, Kal'nov, Kardash. 1 During the last fifteen years, a new area of microelectronics and nanotechnology, the image formation of solid substrates by sharply focused electron beam deposition from a vapor of organometallic (or other metal-containing) precursors have been intensively developed [1][2][3][4]. This technique makes it possible to apply with nanometer-scale accuracy 2D and 3D images with quite various (conducting, die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…For deposits from Fe 3 ͑CO͒ 12 , it was reported that "additional irradiation of high-resistance lines ͑preliminarily deposited at low beam current values͒ at high I values leads to a considerable increase in the conductivity of lines." 91 Similar results were found for deposits from W͑CO͒ 6 , where the resistivity decreased with a factor of 20. 73 Finally, postdeposition irradiation can be used to sculpt a deposit.…”
Section: Extra Irradiationsupporting
confidence: 70%
See 2 more Smart Citations
“…For deposits from Fe 3 ͑CO͒ 12 , it was reported that "additional irradiation of high-resistance lines ͑preliminarily deposited at low beam current values͒ at high I values leads to a considerable increase in the conductivity of lines." 91 Similar results were found for deposits from W͑CO͒ 6 , where the resistivity decreased with a factor of 20. 73 Finally, postdeposition irradiation can be used to sculpt a deposit.…”
Section: Extra Irradiationsupporting
confidence: 70%
“…When the conductivity of deposits is measured as a function of accumulated charge, the general trend is that the resistance decreases with increasing accumulated charge. This is, for instance, the case in measurements by Bruk et al 91 They found that the resistance of wires deposited from Fe 3 ͑CO͒ 12 decreases with increasing accumulated charge. However, since the dimensions of the deposits were not reported, it is not possible to elucidate the mechanism by which the resistance decreased.…”
Section: Conductivitymentioning
confidence: 70%
See 1 more Smart Citation
“…315 Other higher nuclei number iron carbonyls ͓Fe 3 ͑CO͒ 12 ͔ as precursor resulted in nanocomposite deposits, comparable to the simpler carbonyls. 316 The approach of increasing the metal content by increasing the number of metal to metal bonds and decreasing the number of ligands were already developed in focused laser beam 317 or focused ion beam 318,319 induced decomposition of metal organic compounds for multichip interconnects. It did improve the purity of the lines obtained in pyrolytic laser direct writing, but in FIB writing, reasonable electrical properties could only be obtained after reactive thermal annealing.…”
Section: Carbonylsmentioning
confidence: 99%
“…[1][2][3] In an envisioned 3-dimensional memory device, DWs are propagated between discrete sites along a nanostrip, forming a bit shift register with a very high data density. An interesting new route to 3-dimensional nanostructures is provided by focused-electron-beam-induced deposition (FEBID), [5][6][7][8][9][10][11][12][13][14][15][16] a tool that can be used to create nanoobjects of any desired shape. An interesting new route to 3-dimensional nanostructures is provided by focused-electron-beam-induced deposition (FEBID), [5][6][7][8][9][10][11][12][13][14][15][16] a tool that can be used to create nanoobjects of any desired shape.…”
Section: Introductionmentioning
confidence: 99%